Analisis dan Perancangan Sistem Pendukung Keputusan Pemilihan Pemasok Terbaik dari Pemasok Tersedia dengan Metode Analytical Hierarchy Process (AHP): Studi Kasus Divisi Power PT Guna Elektro - Kartawiguna, Daniel; Prayudo, Yohanes Adityo; Sutiono, Maureen; Roesly, Hendry (Bina Nusantara University, 2012)
The purpose of this study is to develop a decision support system to support supplier selection process in PT Guna Elektro and also to develop a system that could provide alternatives to the selection of the best suppliers. The methodologies used in this study are analysis, design, and literature study. Analysis will be done by conducting a survey about the current company system, conducting interviews with system users, and then analyzing the survey results. The literature study is conducted by searching reference sources related to the study while the design is conducted by designing a data management subsystem, model, knowledge base, and user interface. The result on the development of the decision support system application can be used to select the most appropriate supplier which are suitable with the criteria required. The developed decision support system helps support the decision making process for supplier selection.